Interactive valuation: the social construction of the value of ecological services. (1st January 1999) - Jiggins, Janice; Roling, N.
Two different perspectives mark the discourse about the valuation of ecological services: a positivistrealist perspective, emphasising the use of objective scientific procedures to discover true values of ecological services truth is seen as the basis for social change; and a constructivist perspective, emphasising value as emerging from interaction. Value is an agreement and hence effective in social change. This paper examines the implications of the latter for valuation. It first analyses the current dominant practice of environmental valuation in terms of its epistemological assumptions. It then examines how a constructivist perspective colours the expectation of societal effectiveness of environmental valuation. Both themes reflect debated issues in ecological economics (e.g. O'Connor, 1998). "Double hermeneutics" refers to the capacity to make sense on the basis of the sense-making of others. Environmental valuation in economics attempts a sort of "triple hermeneutics": economists make sense of how people value the environment, in order to influence the sense-making of policy-makers and the general public. This paper argues that environmental valuation alternatively can be carried out as a constructivist procedure that reduces triple to single hermeneutics. Environmental valuation aims at societal change through internalisation of the costs of ecological services. Knowledge of the "real" costs is expected to influence behaviour. Our analysis calls for the wider use of an alternative approach "interactive valuation". That is, the people whose behaviour incurs environmental costs are assisted to use environmental valuation methods themselves in order experientially to learn to internalise the environmental costs of their activities. It is not the researcher or expert who analyses and learns, so that he/she can transfer the learning to others, but the "others" themselves who analyse and learn. In practice, this means that scientific valuators are not limited to discovering "real", objective values, but also engage in developing tools for discovery learning by people themselves. The paper elaborates concrete experiences in the analysis and development of farming systems.